If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -7) + 13x + -20 = 8(x + 10) + -15x + 65 Reorder the terms: 5(-7 + 4x) + 13x + -20 = 8(x + 10) + -15x + 65 (-7 * 5 + 4x * 5) + 13x + -20 = 8(x + 10) + -15x + 65 (-35 + 20x) + 13x + -20 = 8(x + 10) + -15x + 65 Reorder the terms: -35 + -20 + 20x + 13x = 8(x + 10) + -15x + 65 Combine like terms: -35 + -20 = -55 -55 + 20x + 13x = 8(x + 10) + -15x + 65 Combine like terms: 20x + 13x = 33x -55 + 33x = 8(x + 10) + -15x + 65 Reorder the terms: -55 + 33x = 8(10 + x) + -15x + 65 -55 + 33x = (10 * 8 + x * 8) + -15x + 65 -55 + 33x = (80 + 8x) + -15x + 65 Reorder the terms: -55 + 33x = 80 + 65 + 8x + -15x Combine like terms: 80 + 65 = 145 -55 + 33x = 145 + 8x + -15x Combine like terms: 8x + -15x = -7x -55 + 33x = 145 + -7x Solving -55 + 33x = 145 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -55 + 33x + 7x = 145 + -7x + 7x Combine like terms: 33x + 7x = 40x -55 + 40x = 145 + -7x + 7x Combine like terms: -7x + 7x = 0 -55 + 40x = 145 + 0 -55 + 40x = 145 Add '55' to each side of the equation. -55 + 55 + 40x = 145 + 55 Combine like terms: -55 + 55 = 0 0 + 40x = 145 + 55 40x = 145 + 55 Combine like terms: 145 + 55 = 200 40x = 200 Divide each side by '40'. x = 5 Simplifying x = 5
| 15x/7=0 | | -[8z-(18z+3)]=3+(9z+10) | | 11x+2=10x+4 | | 92=2h | | X*1+2*0.6=2+X*0.9 | | 2c^2-c-6= | | -196=-9.8x^2 | | 9p+2=4+8p | | 2x+1=-(9) | | 6x^2-23x=7 | | 5k=50 | | 2(3r-6)-(2r+1)=-13 | | q=p(r+s)p | | x^2(x^2-64)-25(x^2-64)=0 | | 2x^2-22x+60=0 | | x+6+x=46 | | -8+3x-2-6x=17 | | F(9)=3(9)+2 | | 7n=16.1 | | -12+f=12 | | 4x-3(6)=12 | | lnx=ln(x-7)+ln(5) | | 2(4r+8)-4(r+3)= | | (3t-4)(3t-4)-7(3t-4)+10=0 | | -3+5x+6=7x-4+5x | | 3+8n-1=-4n+2-5n | | 0=9x^4-25x^2 | | 4x+1=8x-5 | | 0.15x-3=0.3(x-7) | | -12=5-6n+11 | | 14+x=4 | | 50r^2-32= |